Phosphorylation of hepatitis C virus-encoded nonstructural protein NS5A. - Tanji, Y (1995)
Two proteins, a 56-kDa protein (p56) and a 58-kDa protein (p58), are produced from the hepatitis C virus (HCV) nonstructural region 5A (NS5A). Recently, we found that both proteins are phosphorylated at serine residues and that p58 is a hyperphosphorylated form of p56. Furthermore, hyper-phosphorylation depends on the production of an intact form of the HCV NS4A protein. To clarify the nature of NS5A phosphorylation, pulse-chase analysis was performed with a transient protein production system in cultured cells. The study indicated that basal and hyperphosphorylation of NS5A occurred after proteolytic production of NS5A was complete. In an attempt to identify the location of the hyperphosphorylation sites in p58, proteins with sequential deletions from the C-terminal region of NS5A and with mutations of possible phosphorylated serine residues to a neutral amino acid, alanine, were constructed. The deleted or mutated proteins were then tested for hyperphosphorylation in the presence of the NS4A product. Here, we report that serine residues 2197, 2201, and/or 2204 are important for hyper-phosphorylation. Important sites for basal phosphorylation were identified in the region from residues 2200 to 2250 and in the C-terminal region of the NS5A product. A subcellular localization study showed that most of the NS5A products were localized in the nuclear periplasmic membrane fraction.